2022
DOI: 10.3389/fpubh.2022.913636
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking and depressive symptoms in Chinese middle-aged and older adults: Handling missing values in panel data with multiple imputation

Abstract: IntroductionThe high co-occurrence of tobacco smoking and depression is a major public health concern during the novel coronavirus disease-2019 pandemic. However, no studies have dealt with missing values when assessing depression. Therefore, the present study aimed to examine the effect of tobacco smoking on depressive symptoms using a multiple imputation technique.MethodsThis research was a longitudinal study using data from four waves of the China Health and Retirement Longitudinal Study conducted between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…First, our results show that ND positively correlates with anxiety, consistent with previous reports [9,21,37,38]. Although previous studies remain mixed regarding the direction of the association between smoking and mental illness, more and more studies support the view that nicotine exposure is associated with the later onset of depression or anxiety [8,39]. Second, our results revealed that ADPN rs266729 CC homozygous carriers were more likely to suffer from anxiety among ND patients than G allele carriers.…”
Section: Discussionsupporting
confidence: 91%
“…First, our results show that ND positively correlates with anxiety, consistent with previous reports [9,21,37,38]. Although previous studies remain mixed regarding the direction of the association between smoking and mental illness, more and more studies support the view that nicotine exposure is associated with the later onset of depression or anxiety [8,39]. Second, our results revealed that ADPN rs266729 CC homozygous carriers were more likely to suffer from anxiety among ND patients than G allele carriers.…”
Section: Discussionsupporting
confidence: 91%
“…These elements play a role in mood mediation by participating in the synthesis and metabolism of neurotransmitters, reducing inflammation, and stimulating the stress system [ 43 ]. Additionally, physical activity has been shown to effectively intervene and alleviate depressive symptoms through brain-derived neuromolecular mechanisms [ 44 ]. Notably, older adults who smoke and consume alcohol are more prone to depressive symptoms than non-smokers and non-drinkers [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between smoking and depression has been widely documented, such that depression is associated with subsequent smoking behavior and smoking exposure is associated with subsequent depression (An & Xiang, 2015; Wootton et al, 2020). One possible explanation is that smoking or chewing tobacco releases nicotine that affects the neural circuitry of individuals, which increases their susceptibility to depression (Du et al, 2022).…”
Section: Discussionmentioning
confidence: 99%